PDLLA enriched with ulvan particles as a novel 3D porous scaffold targeted for bone engineering - Alves, A. (2012)
A marine derived polysaccharide, ulvan, extracted from green algae, was combined with poly-d, llactic acid (PDLLA) in order to produce a novel scaffold for bone tissue engineering applications. Three dimensional (3D) scaffolds of PDLLA loaded with ulvan particles were originally prepared by subcritical fluid sintering with carbon dioxide at 40 ◦C and 50 bar. Prepared matrixes were characterized in order to validate their suitability to be used as scaffolds for bone tissue regeneration. Characterization included micro-computed tomography, mechanical compression testing, water uptake and degradation testing, and cytotoxicity assays. In addition, ulvan particles loaded with dexamethasone, were also dispersed within the PDLLA matrix and the respective release profile from the samples was evaluated. Prepared PDLLA scaffolds enriched with ulvan particles demonstrated appropriate physicochemical and cytocompatible features to be used for the envisaged applications. On the other hand, the release of dexamethasone from ulvan particles embedded within the PDLLA matrix revealed that the designed systems can be potentially suitable for localized drug delivery. These results further contribute to the establishment of ulvan as a potential novel biomaterial.